Seeking salt: herbivorous prairie insects can be co‐limited by macronutrients and sodium. (23rd July 2018) - Prather, Chelse M.; Laws, Angela N.; Cuellar, Juan F.; Reihart, Ryan W.; Gawkins, Kaitlin M.; Pennings, Steven C.
Abstract: The canonical factors typically thought to determine herbivore community structure often explain only a small fraction of the variation in herbivore abundance and diversity. We tested how macronutrients and relatively understudied micronutrients interacted to influence the structure of insect herbivore (orthopteran) communities. We conducted a factorial fertilisation experiment manipulating macronutrients (N and P, added together) and micronutrients (Ca, Na and K) in large plots (30 × 30 m 2 ) in a Texas coastal prairie. Although no single or combination of micronutrients affected herbivore communities in the absence of additional macronutrients, macronutrients and sodium added together increased herbivore abundance by 60%, richness by 15% and diversity by 20%. These results represent the first large‐scale manipulation of single micronutrients and macronutrients in concert, and revealed an herbivore community co‐limited by macronutrients and Na. Our work supports an emerging paradigm that Na may be important in limiting herbivore communities.